Aesthetics of Lifestyle in the Translated Literary Works of George Orwell - Thi Hang, Truong (Journal of Cultural Approach, 2025)
This article aims to study the aesthetics of lifestyle in the translations of George Orwell’s works, consisting of 6 pieces: 3 fiction and 3 non-fiction. The study reveals Orwell’s perspectives on lifestyle aesthetics in three aspects: the awe of natural beauty, the appreciation of human beauty (physical and spiritual), and the admiration for artistic beauty. It includes Myanmar dance art, Chinese foot-binding art, architectural design in Spain, and the art of tea drinking.